2016
DOI: 10.1055/s-0042-118227
|View full text |Cite
|
Sign up to set email alerts
|

Comparing endoscopic intervention against fully covered self-expanding metal stent placement for post-endoscopic sphincterotomy bleed (CEASE Study)

Abstract: Background and study aims: Limited data exist for the use of fully covered self-expanding metal stent (FCSEMS) as an intervention for immediate bleeds post-endoscopic sphincterotomy (ES) after primary endoscopic intervention failure or to reduce the number of delayed bleeding events in patient with increased risk of bleeding post-ES. Patients and methods: We evaluated a retrospective cohort of individuals who had ES performed from 2011 to 2014. A total of 700 patients were identified with 67 patients having po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
18
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 10 publications
1
18
0
Order By: Relevance
“…There is currently no consensus on when to remove the FCSEMS placed for hemostasis. In most studies, the stent was removed after 1 to 4 weeks, although Cochrane and Schlepp described a longer duration of 88 days . In our series, the stent was removed after an average of 32.2 days.…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…There is currently no consensus on when to remove the FCSEMS placed for hemostasis. In most studies, the stent was removed after 1 to 4 weeks, although Cochrane and Schlepp described a longer duration of 88 days . In our series, the stent was removed after an average of 32.2 days.…”
Section: Discussionmentioning
confidence: 69%
“…Most recently, Cochrane and Schlepp conducted a retrospective nonrandomized controlled comparative study between traditional endoscopic intervention and FCSEMS in patients with post‐ES bleeding. They concluded that FCSEMS can provide hemostasis after the failure of primary endoscopic intervention and reduce the need for high‐risk procedures such as embolization and surgery . Another advantage of this treatment is the simultaneous and effective drainage of the bile duct, especially when occluded with blood clots …”
Section: Discussionmentioning
confidence: 99%
“…To prevent additional tissue injury during hemostasis in HD patients who are at greater risk of bleeding, covered selfexpandable metal stent placement might be useful. 21,22 Despite the insights provided by our study, there are some limitations to consider. First, some candidates were excluded from this study because of deficiencies in their available data.…”
Section: Discussionmentioning
confidence: 83%
“…Cochrane and Schlepp reported a study that compared the effects of FCSEMS and conventional endoscopic therapy for patients with post‐ES bleeding. It shows that FCSEMS can provide hemostasis after primary endoscopic intervention failure, which in turn avoids the more invasive treatment strategies, including TAE and surgery.…”
mentioning
confidence: 99%